Reliability-Based Maintenance Optimization for Transfer Carriage Station in Palm Oil Mills Using FMEA and Fishbone Analysis - Nadya Rishelin; Gustiarini Rika Putri; Galih Prakoso; Viky Kurnia Putri (JTI: Jurnal Teknik Industri, 2025)
Failures in the transfer carriage at the tippler station significantly disrupt material flow in palm oil mills, contributing to approximately 50% of total downtime during seven months of operation. This study aims to identify critical failure components of the transfer carriage system using the FMEA framework, analyze the root causes of these failures through the fishbone diagram and recommend maintenance improvement strategies. Data were collected through maintenance records, direct observation, and SOD questionnaires completed by three experienced personnel. Failure Modes and Effects Analysis (FMEA) was applied to prioritize risks, while a fishbone diagram was used to determine root causes. The analysis showed that bearing damage or broken had the highest RPN (189) and represented the primary cause of operational interruptions. Improvement actions including automatic lubrication, stricter inspections, operator training, and higher-quality bearing selection, are projected to reduce failure frequency and unplanned downtime, enabling a shift from reactive to preventive maintenance while improving asset utilization and production stability This study offers a structured, data-driven framework for enhancing equipment reliability in palm oil mills, with practical relevance for maintenance planning and resource allocation. Keywords: Palm oil mill; transfer carriage; tippler station; FMEA; fishbone diagram; critical component